Using Databases In The Social Studies Classroom - Foyle, Harvey; Yates, Bill (Teaching History: A Journal of Methods, 1993)
The knowledge base in history and the social studies is increasing exponentially. For example, Bosnia-Herzegovina is usually thought of in the context of World War I. Yet with the dissolution of the Eastern European communist block and the disintegration of Yugoslavia, this region is headline news once again. New countries, new capitals, new leaders, and an ever growing array of data. This knowledge explosion necessitates that students learn to manipulate information and make sense out of that information.